Optimization of Fermentation Conditions and Media for Production of Glucose Isomerase from Bacillus megaterium Using Response Surface Methodology - Hoang-Yen Thi Nguyen; Gia-Buu Tran (Scientifica)
Glucose isomerase is an enzyme widely used in food industry for producing high-fructose corn syrup. Many microbes, including Bacillus megaterium, have been found to be able to produce glucose isomerase. However, the number of studies of glucose isomerase production from Bacillus megaterium is limited. In this study, we establish the optimal medium components and culture conditions for Bacillus megaterium glucose isomerase production by evaluating the combined influence of multiple factors and different parameters via Plackett–Burman design and response surface methodology in Modde 5.0 software. The optimized conditions, which were experimentally confirmed as follows: D-xylose (1.116%), K2HPO4 (0.2%), MgSO4·7H2O (0.1%), yeast extract (1.161%), peptone (1%), pH 7.0, inoculum size 20% (w/v), shaking 120 rpm at 36.528°C for 48 hours, give rise to production of highest activity of glucose isomerase (0.274 ± 0.003 U/mg biomass). These results provide additional important information for future development of large-scale glucose isomerase production by Bacillus megaterium.